Flexural behavior of reinforced lightweight aggregate concrete beams - Lim, H. S. (2006)
The research work reported in this paper deals with the flexural response of reinforced lightweight aggregate concrete (LWAC) beams. It consists of testing a total of 11 prototype beams designed to cover a wide range of parameters and address the major design issues, like cracking and crack width, stiffness and deflection and, strength and ductility. The results of these tests, presented and discussed in relation to the use of conventional normal weight concrete (NWC) and a major structural code ACI 318, indicate that the overall response of the LWAC beams used in this study with a density of 1850 kg/m3 closely resembles that of NWC beams and that the major structural code that contain provisions for the use of LWAC give reasonable predictions. The findings of this study should therefore serve as an encouragement for the regional building authorities to consider the use of LWAC to reap its potential benefits.